Peatland Water Processing at State Islamic Senior High School (MAN) 1 Kubu Raya: An Exploration - Kadaria, Ulli; Nugraheni, Putranty Widha; Pramadita, Suci; Aprillia, Ricka; Asbanu, Govira Christiadora (Indonesian Journal of Community Services, 2024)
Madrasah Aliyah Negeri (MAN) 1 Kubu Raya is an education facility in Rasau Jaya District, Kubu Raya Regency. The soil type is peat soil, so the kind of soil also influences the quality of water in the surrounding area. The physical quality of peat water is brown and has sediment. Using peat water for bathing, washing, and toileting purposes will result in a brownish color of the kitchen eating utensils and the bathroom tub. Rasau Jaya District has no water supply from the Regional Public Drinking Water Company, so people use peat water for toilets and rainwater for drinking. The research shows that peat water quality exceeds the required standards, so it must be processed before use. Community Service Activities were conducted at MAN 1 Kubu Raya to educate students in processing peat water. The activities carried out were socialization and simulation of peat water processing with simple processing methods such as coagulation and filtration. Students are expected to apply peat water treatment in school and at home with this simple treatment